2018
DOI: 10.1093/pcp/pcy037
|View full text |Cite
|
Sign up to set email alerts
|

In Concert: Orchestrated Changes in Carbohydrate Homeostasis Are Critical for Plant Abiotic Stress Tolerance

Abstract: The sessile lifestyle of higher plants is accompanied by their remarkable ability to tolerate unfavorable environmental conditions. This is because, during evolution, plants developed a sophisticated repertoire of molecular and metabolic reactions to cope with changing biotic and abiotic challenges. In particular, the abiotic factors light intensity and ambient temperature are characterized by altering their amplitude within comparably short periods of time and are causative for onset of dynamic plant response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(130 citation statements)
references
References 94 publications
3
124
0
Order By: Relevance
“…Yet, underlying biochemical and regulatory mechanisms are less clear [38]. Predominantly, this is due to diverse roles of sugars and involved enzymes in osmoregulation, cryoprotection, membrane stabilization, signalling and ROS scavenging [32,[39][40][41][42][43]. In previous studies, the sucrose biosynthesis pathway was shown to be a limiting factor in cold acclimation [33,41].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, underlying biochemical and regulatory mechanisms are less clear [38]. Predominantly, this is due to diverse roles of sugars and involved enzymes in osmoregulation, cryoprotection, membrane stabilization, signalling and ROS scavenging [32,[39][40][41][42][43]. In previous studies, the sucrose biosynthesis pathway was shown to be a limiting factor in cold acclimation [33,41].…”
Section: Discussionmentioning
confidence: 99%
“…The highly hydroxylated and soluble sugars may generally serve as efficient ROS quenchers and in membranes may be involved in scavenging hydroxyl radicals generated by lipid peroxidation. In response to abiotic stress factors, such as high light or low temperatures, higher plants typically accumulate the disaccharide sucrose as well as the monosaccharides glucose and fructose (Pommerrenig et al, 2018). Sugar alcohols possess more hydroxyl groups than their sugar precursors, and often accumulate in response to oxidative stress (Pommerrenig et al, 2018).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…In response to abiotic stress factors, such as high light or low temperatures, higher plants typically accumulate the disaccharide sucrose as well as the monosaccharides glucose and fructose (Pommerrenig et al, 2018). Sugar alcohols possess more hydroxyl groups than their sugar precursors, and often accumulate in response to oxidative stress (Pommerrenig et al, 2018). The metabolite profile of Zygnema also indicated an accumulation of the sugar alcohols sorbitol and mannitol in the top layer of the mat, which could be a response to ROS formation.…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…8C). Since sucrose fulfills various roles in plant development and stress response (Rolland 488 et al, 2006;Hanson and Smeekens, 2009;Teng et al, 2005) it appears likely that its 489 intracellular homeostasis must be tightly regulated (Pommerrenig et al, 2018). This 490 assumption gained direct support by the recent discovery of a chloroplast located 491 sucrose exporter pSuT, which is involved in fine control of the onset of flowering and 492 frost tolerance of Arabidopsis (Patzke et al, 2019).…”
mentioning
confidence: 99%